274 Effects of Revalor ih/revalor-200 Re-implant Program or Revalor-xh on Performance and Carcass Characteristics of Finishing Heifers Fed for 179, 200, or 221 Days. (7th May 2021) - Nuttelman, Brandon L; Hutcheson, John P; Nichols, Wade T; Streeter, Marshall N; Crawford, Grant I; Walter, Lee-Anne J; Renter, David G; Amrine, David; Depenbusch, Brandon; Wells, Tyler
Abstract: The objective of this study was to compare feedlot performance and carcass traits between two implant programs in heifers harvested at 3 different days on feed (DOF; 179, 200, or 221 d). Crossbred beef heifers (n = 3, 084; 291 + 3.9 kg) were used in a 2×3 factorial arrangement of treatments in a randomized complete block design. Revalor-IH (80 mg TBA and 8 mg E2 ) was administered on arrival followed by Revalor-200 (200 mg TBA and 20 mg E2 ) 94 d before harvest (IH/200) or Revalor-XH (80 mg TBA and 8 mg E2, uncoated; 120 mg TBA and 12 mg E2, coated) was administered on arrival (XH). No implant × DOF interaction was detected (P ≥ 0.09) for any parameter. Heifers subjected to IH/200 had greater (P ≤ 0.01) final BW, ADG (P < 0.01) and G:F (P = 0.01). As DOF increased, BW increased (P ≤ 0.01) while ADG (P < 0.01) and G:F (P ≤ 0.01) decreased. Hot carcass weight was greater (P = 0.01) for IH/200 compared with XH (367 vs. 361 kg, respectively). Heifers receiving XH had greater marbling scores (P = 0.02; 582 vs. 568) and BF (P = 0.01; 1.78 vs 1.70 cm) compared with IH/200 while re-implanted heifers had increased (P = 0.01) REA (86.5 vs. 83.2 cm 2 ). Heifers implanted with XH tended to be fatter than those implanted with IH/200 having a greater (P = 0.01) proportion of USDA Prime and fewer (P < 0.01) USDA Select. Increasing DOF increased (P ≤ 0.03) HCW, DP, BF, REA, marbling, and proportion of USDA Prime carcasses. Growth performance and HCW were increased for IH/200 compared with XH heifers. Increasing DOF resulted in poorer ADG and G:F but increased HCW.